INDUSTRIAL REVOLUTION 4.0 IN NEUROREHABILITATION: THE IMPLEMENTATION OF VIRTUAL REALITY FOR NEUROLOGICAL DISORDERS - Widyadharma, I Putu Eka; Limalvin, Nicholas Prathama; Dharmatika, I Made Pramana; G, Gayathridayawasi; Indrayani, Ida Ayu Sri; Nugraha, Boya (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2021)
Industrial revolution 4.0 has changed the health industry. Medical treatments derived from the latest technologies are expected to improve health and economic status. The rapid development of technology has influenced the learning and clinical practice of medicine. Virtual Reality (VR) is one of the latest technologies that is currently being implemented as a treatment for neurological disorders. This article seeks to give an overview of the development of VR implementation in neurorehabilitation. The data source of this article is research and studies published in NCBI, PubMed, Cochrane, and other relevant online databases. From this article, it is found that VR can be used as a pain reliever and motor function rehabilitation for patients with balance and gait deficits. VR is used to distract patients’ attention to pain for a short time period. VR also improves motor function recovery in stroke patients. Cybersickness is usually reported as a side effect of using VR and it depends on each individual. The implementation of VR for patients with neurological disorders has showed advantages in reducing pain and improving motor function but still need further research about applicability and authorization of virtual reality in the world of medicine.